Characteristics of inceptisol ameliorated with rice husk biochar to glyphosate adsorption - Herviyanti, Herviyanti; Maulana, Amsar; Lita, Arestha Leo; Prasetyo, Teguh Budi; Monikasari, Moli; Ryswaldi, Ridho (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2022)
As an ameliorant, rice husk biochar (RHB) can improve soil quality and long-term carbon absorption and interaction with glyphosate during adsorption. This study investigated the ability of Inceptisol ameliorated with RHB to absorb glyphosate. Inceptisol ameliorated with 40-t ha-1 RHB increased the soil surface charge (ΔpH) by improving soil pH H2O, electrical conductivity, cation exchange capacity, and soil organic matter. Linear and nonlinear models showed that fitting Langmuir and Freundlich isotherms is suitable for this study. The isotherm adsorption of glyphosate sequentially occurs in the Freundlich and Langmuir models (Inceptisol + 40-t ha-1 RHB > Inceptisol), where the Freundlich model (R2 = 0.938) is dominated by glyphosate adsorption on Inceptisol + 40-t ha-1 RHB with n of 0.46 and KF of 1.747 mg kg-1, whereas the Langmuir model (R2 = 0.8608) with Qm of 30.01 mg kg-1 and KL of 0.08 L mg-1 at a concentration level of 100 ppm and pH of the glyphosate solution 5.20 units. The glyphosate adsorption was also supported by changes in functional groups, where Fourier transform infrared spectroscopy shows a decrease in transmittance in the O-H; C=C; C-O; C-H, and mineral groups, indicating an increase in the adsorption capacity in Inceptisol ameliorated with 40-t ha-1 RHB. This study indicated that the physicochemical properties of Inceptisol are important in controlling the glyphosate adsorption ability of RHB in soils.